2018
DOI: 10.21307/sjcapp-2018-006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of children with autism who received different forms of early intervention during their preschool years: a pilot study of 15 young adults

Abstract: Background: Studies on early intervention have reported significant gains for many children with autism. Knowledge on how these children fare in adulthood is limited. Objective: To examine long-term outcome of children with autism who received different forms of early intervention. Method: Participants were 15 young people who had all been diagnosed with ICD-10 childhood autism during the preschool years. Five received intervention based on the UCLA model for early intensive behavioral intervention, and 10 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Gibson & Douglas, 2018 ; Kirkham, 2017 ), this investigation was the beginning of the now widespread field of applied behavior analysis (ABA), which remains one of the most widely used interventions for skill acquisition and reduction of harmful behavior for Autistic individuals today (Becerra et al, 2017 ; Xu et al, 2019 ). While this traditional form of ABA therapy (commonly referred to as Discrete Trial Training [DTT; Smith, 2001 ]) has been shown to have some beneficial effects on outcomes such as language, social functioning, adaptive behavior, cognitive ability, and challenging behaviors (Sandbank et al, 2020 ), there is a paucity of experimental evidence regarding long-term effects on adult outcomes (Jónsdóttir et al, 2018 ). Moreover, the literature has identified issues with some aspects of DTT’s implementation and outcomes, including slow progress, some practitioners’ continued use of aversives, and the potential lack of generalization and flexible application of skills in naturalistic contexts (Kirkham, 2017 ; Koegel et al, 1998 ; Sandoval-Norton & Shkedy, 2019 ; Schreibman, 2005 ).…”
Section: History Of Autism Interventionmentioning
confidence: 99%
“…Gibson & Douglas, 2018 ; Kirkham, 2017 ), this investigation was the beginning of the now widespread field of applied behavior analysis (ABA), which remains one of the most widely used interventions for skill acquisition and reduction of harmful behavior for Autistic individuals today (Becerra et al, 2017 ; Xu et al, 2019 ). While this traditional form of ABA therapy (commonly referred to as Discrete Trial Training [DTT; Smith, 2001 ]) has been shown to have some beneficial effects on outcomes such as language, social functioning, adaptive behavior, cognitive ability, and challenging behaviors (Sandbank et al, 2020 ), there is a paucity of experimental evidence regarding long-term effects on adult outcomes (Jónsdóttir et al, 2018 ). Moreover, the literature has identified issues with some aspects of DTT’s implementation and outcomes, including slow progress, some practitioners’ continued use of aversives, and the potential lack of generalization and flexible application of skills in naturalistic contexts (Kirkham, 2017 ; Koegel et al, 1998 ; Sandoval-Norton & Shkedy, 2019 ; Schreibman, 2005 ).…”
Section: History Of Autism Interventionmentioning
confidence: 99%
“…However, it is also important to note that early intervention may need to be paired with ongoing supports and intervention in order to ensure that gains persist into adulthood. For example, in one longitudinal study that included three phases of assessment, researchers found "significant gains" (i.e., IQ gains and decreased symptomology) at age 6 compared to a group with dissimilar interventions; however, these positive contrasting gains disappeared in early adulthood (Jónsdóttir, Brynjarsdóttir, Saemundsen, & Sigurdsson, 2018). It is also essential to realize that some parents disagree with the emphasis placed on one model of intervention and its focus in the early years and that some adults with ASD are also speaking out about negative childhood experiences related to (E)IBI (Dawson, 2004;Langan, 2011).…”
Section: (Early) Intensive Behaviour Interventionmentioning
confidence: 99%
“…Gillberg and Steffenburg (1987) reported that an IQ of more than 50 distinguished those with fair or better outcomes from those with poor or very poor outcomes; Howlin et al (2004) found that those with a poor or very poor outcome had a performance IQ (PIQ) below 70 and verbal IQ (VIQ) below 50. Having a higher IQ in adulthood is also associated with better outcome (Cederlund et al 2008;Eaves and Ho 2008;Howlin et al 2013;Jónsdóttir et al 2018). Eaves and Ho (2008), Howlin et al, (2013) and Farley et al (2009) report significant correlations (ranging from 0.40 to 0.65) between measures of IQ and outcome.…”
Section: Introductionmentioning
confidence: 97%
“…Howlin et al (2013) found that retrospective information on early autism severity was a stronger predictor of outcome than either childhood language ability or childhood IQ. Helles et al (2017) and Jónsdóttir et al (2018) reported that autism severity (measured at mean age 29.9 and 6.0 years respectively) negatively correlated with outcome. Chamak and Bonniau (2016) also reported that "high functioning" autism/Asperger's was exclusively associated with good outcome, and those who had "moderate autism" or "severe autism" were more likely to have poor or very poor outcome.…”
Section: Introductionmentioning
confidence: 99%